Saúde mental relacionada ao trabalho no Centro Estadual de Referência de Saúde do Trabalhador de Mato Grosso (MT) - Conciani, Marta Ester (2013)
The Mental Health Related to the Work (SMRT) is an interdisciplinary field of studies that has the human work and its relationships with the processes of mental health-disease as its object. It is consistent with Worker Health’s (ST) , when considering the historicity presented and lived by the workers, inserted or not in the job market, and in the different contexts; and also in the effects that the precarious work has on them. The ST is constituted around the range and the articulation of three main fields: the knowledge one; the technical and political one; and the interventions and practices one. It is based on the principles of Brazil’s National Health System (SUS) and it is organized through the National Network for Worker’s Whole Health Care (RENAST). The principal coordinators are the Worker’s Health Referral Centers (CEREST’S), which are units specialized in the worker's health. This work aims at analyzing the incorporation of SMRT at CEREST of Mato Grosso (CEREST/MT), through documental research, participant observation concerning the organization of the work; and of the identification of the conceptions on the relation between work and mental health-disease. It is based on the assumption that work occupies central position in the lives of people. Methodologically, it relied upon the communicative acting applied to the health management. Results have demonstrated that, different from the national level, there are no elements of the communicative process present in the documents of state coverage; the work process directed to SMRT actions is fragile and the institutional agents do not recognize them as being part of such a field. Several conceptions about work, mental health and SMRT were found. The damage of the absence of the communicative action aimed at the worker's mental health, in the context of CEREST/MT, begins with a conceptual fragility that resounds in the sub-notification of the mental disorders related to the work and in the actions that arrive or stop arriving to the user of SUS. That damage can be understood as a failure in the process of interaction and agreement of the norm between the federal and state levels demonstrating that institutionally the wholeness of the negotiation processes was not reached. The absence of a SMRT hegemonic conception limits the acting of the subjects and it interferes in the accomplishment of compatible actions with the guarantee of labor rights.